Journalists' questions during the Public Health Agency of Sweden's press conferences during the corona pandemic 2020 - Dahlgren, Peter M. (University of Gothenburg, 2021)
This dataset contains questions/turn-takings asked by journalists during the Public Health Agency of Sweden's press conferences during the corona pandemic throughout 2020, as well as during personal interviews with government representatives (mainly the Public Health Agency) on Aftonbladet's web TV and on Sveriges Television's live TV broadcasts. The purpose was to investigate the proportion of journalists' questions that were critical. The data is collected through a quantitative content analysis coded by hand by an individual coder. A total of 1,215 questions / turn-takings (with 26 variables) were asked by journalists, collected during the period 2020-03-06 to 2020-12-29.

The dataset contains raw data, R scripts with comments and plotted graphs. Refer to the documentation file README.pdf (Swedish) for descriptions of individual files.

Detta dataset innehåller frågor/turordningar som ställdes av journalister under Folkhälsomyndighetens presskonferenser under coronapandemin under hela 2020, samt under personliga intervjuer med myndighetsföreträdare (främst Folkhälsomyndigheten) i Aftonbladets webb-tv och i Sveriges Televisions direktsända tv-sändningar. Syftet var att undersöka hur stor andel av journalisternas frågor som var kritiska. Datan är insamlad genom en kvantitativ innehållsanalys som kodats för hand av en enskild kodare. Totalt ingår 1 215 frågor/turordningar (med 26 variabler) som ställdes av journalister, insamlade under perioden 2020-03-06 till 2020-12-29.

Datasetet innehåller rådata, kommenterade R-skript och plottade figurer. Se dokumentationsfilen README.pdf för beskrivning av individuella filer.
Journalisternas frågor under Folkhälsomyndighetens presskonferenser under coronapandemin 2020
Keywords: PUBLIC HEALTH; FOLKHÄLSA; PUBLIC OFFICIALS; ÄMBETSMÄN; CONTENT ANALYSIS; INNEHÅLLSANALYS; JOURNALISTS; JOURNALISTER; COVID-19; COVID-19; Specific diseases, disorders and medical conditions; Specifika sjukdomar, störningar och medicinska tillstånd; Media; Media; Media and Communications; Medie-, kommunikations-, och informationsvetenskaper; Media and Communication Studies; Medie- och kommunikationsvetenskap; Public health; Folkhälsa; Public Health, Global Health and Social Medicine; Folkhälsovetenskap, global hälsa och socialmedicin